Fracture strength of flared bovine roots restored with different intraradicular posts - Clavijo, Victor Grover Rene [UNESP]; dos Santos Nunes Reis, Jose Mauricio [UNESP]; Kabbach, William [UNESP]; Faria e Silva, Andre Luis; Oliveira Junior, Osmir Batista de [UNESP]; Andrade, Marcelo Ferrarezi de [UNESP] (Universidade de São Paulo (USP), Faculdade de Odontologia de Bauru, 2009)
Objective: The aim of this study was to evaluate the fracture strength and failure mode of flared bovine roots restored with different intraradicular posts. Material and Methods: Fifty bovine incisors with similar dimensions were selected and their roots were flared until 1.0 mm of dentin wall remained. Next, the roots were allocated into five groups (n=10): GI-cast metal post-and-core; GII-fiber posts plus accessory fiber posts; GIII-direct anatomic post; GIV-indirect anatomic post and GV-control (specimens without intraradicular post). A polyether impression material was used to simulate the periodontal ligament. After periodontal ligament simulation, the specimens were subjected to a compressive load at a crosshead speed of 0.5 mm/min in a servo-hydraulic testing machine (MTS 810) applied at 135 to the long axis of the tooth until failure. The data (N) were subjected to ANOVA and Tukey's post-hoc test (alpha=0.05). Results: GI and GIV presented higher fracture strength (p<0.05) than GII. GIII presented intermediate values without statistically significant differences (p>0.05) from GI, GII and GIV. Control specimens (GV) produced the lowest fracture strength mean values (p<0.05). Despite obtaining the highest mean value, GI presented 100% of unfavorable failures. GII presented 20% of unfavorable failures. GIII, GIV and GV presented only favorable failures. Conclusions: Although further in vitro and in vivo studies are necessary, the results of this study showed that the use of direct and indirect anatomic posts in flared roots could be an alternative to cast metal post-and-core.
Keywords: Post and core technique; Compressive strength; Prosthodontics